Waist-based anthropometric measures and central adiposity-related comorbidities in children - Howard Gomwe; Lesego Phiri; Chioneso S. Marange (South African Family Practice)
Background: Waist-related measures are commonly used to classify central adiposity and related comorbidities. This classification may be essential among children, as it may identify the risk of future non-communicable diseases.